STEAM and Digital Storytelling: a case study with high school students in the context of Education 4.0 - Silva, Deivid Eive; Sobrinho, Marialina Corrêa; Valentim, Natasha Malveira C. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2019)
Today's professionals need to be trained for more than repetitive activities. Therefore, it is the school's role to promote activities that enable students to think creatively and innovatively. So, they can develop the skills and competences that are required in the 21st Century. This redefines Education, known as Education 4.0. In this paper, we present a case study that was carried out to introduce didactic 4.0, to promote greater engagement in High School. Students followed the STEAM methodology (an acronym for Science, Technology, Engineering, Arts and Mathematics), being able to work skills more interactively and autonomously, through the production of Digital Storytelling (DS). After the study, a qualitative analysis of the results was performed. This analysis indicated that the activities with STEAM and DS helped the students to be more participative and interested in their learning. These methodologies allowed to disseminate the contents of created narratives and to stimulate some skills and competences of the 21st Century. Therefore, it is hoped to create partnerships with teachers from other subjects to carry out new activities in 4.0 format. In this way, be able to involve other technologies, such as robotics, augmented reality, gamification, in order to provoke positive changes in the educational scenario.